Assessment of woody species diversity and composition along a disturbance gradient in Behali Reserve Forest of Biswanath district, Assam, India - Borah, Dipankar; Das, Biswajit; Tangjang, Sumpam; Das, Abhaya Prasad; Khapugin, Anatoliy A. (Ecological Questions, 2020)
The present study was carried out in Behali Reserve Forest, a semi-evergreen forest of Assam, India to record and analyze the woody species diversity and community characteristics using random sampling. Altogether, 35 quadrats (20 m × 20 m) were randomly established and studied from August 2018 to April 2019 spreading across nine study sites. A total of 128 (118 identified and 10 unidentified) woody species from 83 genera and 43 families were found in the sampled area of 1.4 ha. Lauraceae with 19 species was the richest family by species followed by Euphorbiaceae and Phyllanthaceae (eight species each). Altogether, 787 individuals were recorded from the sampled plots and the stand density ranged between 250 individuals × ha-1 to 725 individuals × ha-1 with mean stand density of 543 individuals × ha-1. Species-wise density analysis revealed that Magnolia hodgsonii (96.43 individuals × ha-1) has the maximum tree density. Plot wise analysis showed that Dikal (58.32 m2 × ha-1) recorded the maximum basal area as well as the equitability index of 0.95. In Serelia, we recorded the highest Simpson index (0.92), Shannon H index (2.76), Brillouin index (2.11), Menhinick (3.49), Margalef (5.29) and Fisher alpha index (26.59). In Radhasu, we recorded maximum evenness (0.90), dominance (0.58) and Berger-Parker index (0.65). The maximal values of Chao index (38.53) was recorded in Hatimara. Our study also revealed that diversity was maximal for the community under medium level of disturbance in the reserve, while communities under the lowest and highest disturbance pressure had minimal diversity. The Behali Reserve Forest exhibited a great species richness (118 species), mean basal area (44.42 m2 × ha-1) and stand density (in total, 788 individuals per study area of 1.4 ha) compared to the other forests of the northeastern region of India.